REALIZATION OF THE REQUIREMENTS OF EUROPEAN CERTIFICATE IN PSYCHOLOGY IN PREPARING PRACTICAL PSYCHOLOGISTS IN UKRAINE - Lozova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article examines the experience of implementation of requirements of the «European Certificate in Psychology» in educational programs of Borys Grinchenko Kyiv University. The upgrade of educational programs is described in the context of unification with European standards for future psychologists training. Programmatic innovations designed to provide for necessary qualifications and competitiveness of future MA holders. Program consist of modules which include: compulsory subjects aimed at creating general and professional competences, optional subjects, different practices and the final student examination. The purpose of the article is to present the experience of practical implementation of educational and professional training program for practical psychologists as the first one in Ukraine that meets the requirements of EuroPsy. The method of proving the effectiveness of the Program was a statistical comparison of performance indicators and quality of students' knowledge conducted in 2016-2017 and 2018-2019 academic years. A comparative analysis of students' marks obtained during two academic years showed the effectiveness of the program. Estimates show a positive trend with the number of «excellent» and «good» marks increasing by 12.64% and 4.59% respectively, and «satisfactorily» marks decreasing by 8.05%. It was concluded that the main contributing factor in the improvement was the students' training in the program.